Review of Maritime Transport 1978 - United Nations Conference on Trade; Development (United Nations, 1978)
This annual review identifies the main development in world maritime transport and provides world-wide statistical data. It takes a look at supply/demand equilibrium in containerized shipping, shipbuilding and ship scrapping, the development of ports, privatization and freight markets among other relevant areas. It also presents extracts of the United Nations Code of Conduct as it relates to the areas discussed.